Assessment of local treatment modalities for FIGO stage IB-IIB cervical cancer: A propensity-score matched analysis based on SEER database - Xing Song (Nature Portfolio, 2017)
Abstract The aim of this study was to investigate the impact of local treatment modalities on the survival of patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB-IIB cervical cancer, including cancer-directed surgery (CDS) alone and CDS combined with radiotherapy (RT). A total of 8,357 patients with cervical cancer between 1988 and 2013 were included in the final study cohort, including 4,298 (51.4%) patients who underwent CDS alone and 4,059 (48.6%) patients who received combination therapy. Univariate and multivariate analyses showed that local treatment modalities were prognostic factors for cause-specific survival (CSS). Patients who received combination therapy had worse CSS (HR = 1.38; 95% CI = 1.20–1.59; P < 0.001). Subgroup analyses showed the prognostic effect of local treatment modalities was significantly influenced by FIGO stage. In the propensity-score matched (PSM) dataset, CDS was associated with better CSS (P < 0.001) for patients with IB-IIA cervical cancer; nevertheless, no differences were observed in CSS (P = 0.639) for patients with IIB cervical cancer. In conclusion, radical surgery was the preferred treatment for patients with IB-IIA cervical cancer, and there was no difference between radical surgery alone and combination therapy for patients with IIB cervical cancer.